STATUS KESEHATAN GIGI DAN MULUT ANAK TUNA NETRA DI YAYASAN YAKETUNIS YOGYAKARTA - , MARIA OLIVIA SANDRA; , drg. Sri Widiati, MPH. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Visual impairment leads to an obstacle in the practice of oral hygiene. Children with visual impairment have a worse oral health status compared with sighted children in general. The aim of this study was to find out the difference of oral hygiene status in total blind, low vision, and sighted children. This study used a cross sectional design.Subjects were 90 children aged 12- 22 years old (30 total blinds, 30 low visions, and 30 sighted). Sampling was performed by total sampling and simple random sampling according to inclusion criteria. Oral health status examined were oral hygiene status (OHI-S), caries status (DMFT), and gingivitis status (GI). Data was analyzed using ANACOVA test. The result of the study showed there was a difference of oral hygiene status between total blinds with low visions (p=0,002), total blinds with sighted (p=0,001), and low visions with sighted (p=0,001). There was a difference of caries status between total blinds with low visions (p=0,027) and total blinds with sighted (0,004). There was no difference of caries status between low visions with sighted (p=0,485). There was a difference of gingival status between total blinds with low visions (p=0,002), total blinds with sighted (p=0,001), low visions with sighted (p=0,007). In conclusion, total blind children had the worst oral hygiene status and gingival status meanwhile sighted had the best one. The best caries mean was in sighted children meanwhile the worst one was in blinds.